2022
DOI: 10.1001/jamanetworkopen.2022.19926
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Muscle Mass With Cognitive Function During a 3-Year Follow-up Among Adults Aged 65 to 86 Years in the Canadian Longitudinal Study on Aging

Abstract: IMPORTANCE Cross-sectional studies have shown that combined low muscle mass and strength are associated with cognitive impairment. Whether low muscle mass, reflective of physiologic reserve, is independently associated with faster cognitive decline remains unknown. OBJECTIVE To investigate the associations between low muscle mass and cognitive decline in 3 distinct domains among adults aged at least 65 years. DESIGN, SETTING, AND PARTICIPANTS The Canadian Longitudinal Study on Aging is a prospective population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…It is, therefore, possible that any relationship between lower muscle mass and cognitive function may depend on the stimulus for muscle gain and resulting changes in neuromuscular function or strength. In support of this, a recent longitudinal cohort study similarly identified an inverse association between muscle mass and cognitive function; however, this association was attenuated once adjusted for grip strength 15 . Higher levels of leg strength have also been shown to correlate with better Mini‐Mental State Examination scores and executive functions, and whole‐body strength is positively associated with scores in cognitive test batteries 22 .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is, therefore, possible that any relationship between lower muscle mass and cognitive function may depend on the stimulus for muscle gain and resulting changes in neuromuscular function or strength. In support of this, a recent longitudinal cohort study similarly identified an inverse association between muscle mass and cognitive function; however, this association was attenuated once adjusted for grip strength 15 . Higher levels of leg strength have also been shown to correlate with better Mini‐Mental State Examination scores and executive functions, and whole‐body strength is positively associated with scores in cognitive test batteries 22 .…”
Section: Introductionmentioning
confidence: 87%
“…Using Canadian‐specific cutoffs (<7.30 kg/m 2 for males and < 5.42 kg/m 2 for females), Tessier et al. recently showed that low ALMI was associated with the rate of cognitive decline 15 . This resulted in around 20% of their cohort of adults aged 65−80 having low ALMI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle secretes circulating myokines in response to exercise, that have a role in molecular and cellular neuroprotective processes in the brain, including the expression and regulation of BDNF, among others ( 87 89 ). Indeed, significant associations have been identified between sarcopenia and cognitive decline in healthy aging cohorts ( 90 92 ). Fontan-associated myopenia is a recently established phenomena ( 93 ) and may contribute to the myriad of risk factors associated with Fontan physiology and reduced cognitive functioning.…”
Section: Neural Mechanisms Underpinning the Exercise-cognition Relati...mentioning
confidence: 99%
“…GDF11 seemed to be a crucial element of the young blood in both instances. In older adults, low muscle mass is associated with diminished cognitive function [4].…”
mentioning
confidence: 99%